APLIKASI PENGOLAHAN DATA PEMBAYARAN RETRIBUSI ANGKUTAN PENUMPANG PADA TERMINAL ALAM BARAJO KOTA JAMBI - Lucy Simorangkir; Rendi Saputra (JURNAL AKADEMIKA)
Retribution is a burden or costs awarded to a person in a country who receive certain services or facilities. Retribution is more specific, such as someone getting a particular service, then it must pay a fee on a regular basis. Terminal Alam Barajo Jambi City of Edinburgh is one of the terminals that are precisely located in the province of Jambi in Jambi located at Simpang area Rimbo City of Edinburgh, the terminal is set in the land transportation of passengers and arrange bus transportation levy acceptance of each bus passengers who will pass through or towards the town of Jambi, so the Terminal Alam Barajo including passenger terminals. To produce an effective and efficient information, hence the need for a computer program that is a Microsoft Visual Basic 6.0 is used to process payment data such levies. Where more secure data storage and delivery of information will be faster.